Pengaruh Pelatihan Dan Pengembangan Terhadap Kinerja Karyawan Departemen Produksi Pada PT. Kaltim Diamond Coal Site Loa Gagak Kutai Kartanegara - Wijayanti Wijayanti Wijayanti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The results of the analysis using multiple linear regression equations show the following regression equation: Y = 5.622 + 0.488 (X1) + 0.329 (X2). Data collection techniques are based on the source, including primary data through observation, interviews, questionnaires or questionnaires, and include documentation. Secondary data, among others, by searching for literature in the form of previous research journals, and textbooks that are related to the variables to be studied. The data analysis technique used the validity test, reliability test, and classical assumption test. As for the data analysis technique method using Multiple Linear Regression, Correlation Analysis, Analysis of Determination (R2), hypothesis testing using the F test, T test and variable test which have the most influence. The results showed that the Training (X1) and Development (X2) variables simultaneously had a significant effect on the Employee Performance (Y) of the Production Department of PT. Kaltim Diamond Coal Site Loa Gagak Kutai Kartanegara.“The results of multiple linear regression tests simultaneously found that the Training and Development variables had a significant effect on the Employee Performance of the Production Department“at PT. Kaltim Diamond Coal Site Loa Gagak”Kutai Kartanegara.”The results of”the multiple linear regression test partially found that training and development had a significant influence on the performance of the production department“employees at PT. Kaltim Diamond Coal Site Loa Gagak Kutai Kartanegara”. The results of the most influential variable test, it is known that the training variable is the variable that has the most dominant influence on the Employee Performance of the Production Department at PT. Kaltim Diamond Coal Site Loa Gagak Kutai Kartanegara.